Women's Agency and the Shadow of Patriarchal Domination: Reflections on Kinokawa by Ariyoshi Sawako - Nina Alia Ariefa (IZUMI, 2024)
Kinokawa (The River Ki) is Ariyoshi Sawako's first work, which is about three generations of Japanese women living in different eras. Ariyoshi's efforts in writing this novel are evident through the plot which tells the stories of women who lived during this period. Ariyoshi describes in detail the aspects of humanity affected by the rapid changes of the times. Like the seemingly calm Ki River that hides swirling currents underneath, this novel reveals the story of women who strive to cope with the dynamic changes of the times. In analysis, this study uses a feminist literary criticism approach, focusing on the stories of three female characters, Hana, Fumio, and Hanako. In addition to showing the gap between generations and is influenced by epochal changes toward Japan's new age, this study also reveals the dominant representation of women's agency. Through this novel, Ariyoshi exposes the demands that others and Japanese women place on themselves and reveals their strength. With a strong yet calm voice, Ariyoshi develops vivid female characters that make their mark in a world dominated by men. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor